Development of a simple host-free medium for efficient prezoosporulation of Perkinsus olseni trophozoites cultured in vitro. (February 2021) - Maeda, Kazuki; Yoshinaga, Tomoyoshi; Itoh, Naoki
Abstract: The parasitizing stage (trophozoite) of the protozoan parasite Perkinsus olseni progresses to the dormant stage (prezoosporangium) immediately after the death of the host through physiologically and morphologically drastic changes. This development is reproducible in Ray's fluid thioglycollate medium (RFTM). In this study, supplementation with tissue extract from a host, the Manila clam, significantly improved the efficiency of development, as determined by the numbers and sizes of developed prezoosporangia. Similar results were seen following supplementation with boiled host tissue extract, which indicates that a thermally stable component of the host is required for the parasite's development. Subsequently, we found that a commercially available lipid concentrate significantly increased prezoosporulation without host tissue, suggesting that the lipids in host tissue enhance prezoosporangia development. Moreover, we determined that yeast extract, sodium thioglycollate, and sodium chloride were the only components of RFTM required for prezoosporulation. Based on these findings, we prepared a simple, host-free medium for P. olseni prezoosporulation—Lipid concentrate Yeast extract Medium (LpcYM)—consisting of yeast extract, lipid concentrate, sodium thioglycollate, and sodium chloride. We confirmed that the prezoosporangia developed in LpcYM produce zoospores that are infectious to Manila clams and that trophozoites of other Perkinsus species ( P. marinus, P. honshuensis, and P. chesapeaki ) also develop to prezoosporangia in this host-free medium. As LpcYM has the simplest composition of prezoosporulation media available thus far, it enables us to conduct molecular and biochemical studies examining the drastic transformation process of this parasite. Graphical abstract: Unlabelled Image Highlights: Perkinsus olseni requires lipid concentrate and yeast extract for in vitro prezoosporulation. A simple medium for prezoosporulation, LpcYM, was developed. Infective zoospores were produced in prezoosporangia developed in LpcYM. LpcYM can be used for prezoosporulation of three other Perkinsus species.